Pengaruh Coaching dan Mentoring terhadap Kinerja Karyawan dengan Mediasi Motivasi Kerja di Bank Negara Indonesia Cabang Muara Bungo - Usman, Usman; Suryani, Arna; Akbar, Ali (Universitas Batanghari, 2024)
The objectives of this study are to characterize coaching and mentoring, work motivation, and employee performance at the Bank BNI Muara Bungo Branch. Additionally, work motivation will be used as a mediating variable to examine the effects of coaching and mentoring on employee performance. Descriptive verification research is employed in this kind of study. This study aims to investigate the impact of mentoring on work motivation, which serves as a mediating variable for employee performance at the Bank BNI Muara Bungo Branch. The PLS analysis method is applied in this study. According to the Bank BNI Muara Bungo Branch's description of coaching, mentoring, work motivation, and employee performance, coaching demonstrates the right category, mentoring demonstrates the right category, work motivation demonstrates the high category, and employee performance demonstrates the high category. Counseling has a positive and significant effect on work motivation, work motivation has a positive and significant effect on employee performance, and work motivation has a positive and significant effect on employee performance, according to the research findings. At the Bank BNI Muara Bungo Jambi Branch, mentoring significantly and favorably affects employee performance through work motivation, but coaching has no discernible impact on this.